Antiproliferative Copper(II) and Platinum(II) Complexes with Bidentate N, N‐Donor Ligands. Issue 24 (29th June 2017) - Sommerfeld, Nadine S.; Gülzow, Jana; Roller, Alexander; Cseh, Klaudia; Jakupec, Michael A.; Grohmann, Andreas; Galanski, Markus; Keppler, Bernhard K.
Abstract : Three copper(II) complexes of a series of bidentate dipyridylmethane ligands, as well as their structurally related platinum(II) analogues, have been synthesised and fully characterised to evaluate their coordination chemistry and antiproliferative properties. New crystal structures of the complexesL 3 CuCl2, L 2 PtCl2 andL 3 PtCl2, whereL 2, L 3 have one and two methyl substituents on the bridgehead carbon atom between the coordinated pyridine ligands, respectively, were obtained. The in vitro cytotoxicity of the free ligands and their corresponding platinum and copper complexes was evaluated in the cisplatin‐sensitive ovarian teratocarcinoma cell line CH1/PA1, as well as in rather cisplatin‐insensitive colon (SW480) and lung (A549) carcinoma cells, using the MTT assay. All six complexes showed higher cytotoxicity than the ligandsL 1 –L 3 alone, giving IC50 values in the low micromolar range. Abstract : The coordination chemistry and antiproliferative properties of three copper(II) complexes and their structurally related platinum(II) analogues were investigated. All complexes showed a cytotoxicity higher than those of the ligands alone, giving IC50 values in the low micromolar range. Platinum(II) complexes were about half as potent as cisplatin, but more cytotoxic than their copper(II) counterparts.